GOTHIC ELEMENTS IN DARK SHADOWS MOVIE - Elisha, Nur; Surya, Satyawati; Nasrullah, Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
Gothic stories have a distinctive feature of presenting suspense and horror elements in each of their elements that make the audience both scared and curious as they watch the scenes in a Gothic movie. This research examines Gothic elements in Dark Shadows (2021) movie. The purpose of this study is to identify the Gothic elements in the Dark Shadows (2012) movie. This research used structuralism approach to determine the intrinsic elements and the theory of Gothic elements from Robert Harris in identifying the Gothic elements contained in the Dark Shadows (2012) movie. The method of data analysis is descriptive qualitative research. The data used in this research were taken from the narrative, monologue, dialogue in the script, and the actions of the six main characters in the Dark Shadows (2012) movie directed by Tim Burton. The results of this study indicate that there are nine from eleven Gothic elements found in the Dark Shadows movie. All the nine Gothic elements in this movie displayed in five intrinsic elements.